Immunotherapy Potentiates the Effect of Chemotherapy in Metastatic Melanoma—A Retrospective Study - Hadash-Bengad, Reut; Hajaj, Emma; Klein, Shiri; Merims, Sharon; Frank, Stephen; Eisenberg, Galit; Yakobson, Alexander; Orevi, Marina; Caplan, Nadia; Peretz, Tamar; Lotem, Michal; Cohen, Jonatan E. (Frontiers in Oncology, 2020)
Melanoma survival increased with targeted- and immunotherapy agents, yet the majority of patients ultimately progress and require salvage therapy. In our experience, some patients with progressive disease on immune-checkpoint inhibitors (ICI’s), demonstrate deep and sustained responses to chemotherapy. We hypothesized that ICI’s improve the response to subsequent chemotherapy in metastatic melanoma. We conducted a retrospective study, comparing the efficacy of chemotherapy given with or without prior immunotherapy; we measured progression free survival (PFS), overall survival and response rate. Immune-monitoring was performed on sequential peripheral blood mononuclear cell samples from a chemotherapy-responsive patient. The chemotherapy post-immunotherapy group (CpI) included 11 patients, the chemotherapy without prior immunotherapy (CNPI) group included 24 patients. Median PFS was 5.2 months in the CpI vs. 2.5 months in the CNPI groups; HR 0.37 (95% Confidence interval [CI] 0.144-0.983), P=0.046. Immune-monitoring showed an increased proportion of CD8+ cells, with elevated PD-1 and CD69 expression while on chemotherapy, as compared with all-time points on ICIs, suggesting immune-activation. Immunotherapy potentiates the effect of chemotherapy in metastatic melanoma possibly through activation of CD8+ T cells.